2008
DOI: 10.1002/qua.21833
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of electronic spectra of [Pt3(μ‐CO)3(CO)3] (n = 3–5) complexes

Abstract: ABSTRACT:The platinum-platinum attraction and the spectroscopic properties of [Pt 3 (-CO) 3 (CO) 3 ] n Ϫ2 (n ϭ 3-5) were studied at the PBE level. Theoretical calculations are in agreement with experimental geometries. The absorption spectra of these platinum complexes were calculated by the single excitation time-dependent (TD) density functional method. All complexes showed MLCT transitions interrelated with the intertriangular complexes. The values obtained at the PBE level are in agreement with the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…(7) The present PBE result (first band at 580 nm) is very different from the RI-PBE result of ref (520 nm). This difference can be attributed to the C 2 v constraint of the geometry optimization, but more plausibly to the RI-PBE approximation of ref .…”
Section: Absorption Spectra Of the Chini Clusterscontrasting
confidence: 90%
See 2 more Smart Citations
“…(7) The present PBE result (first band at 580 nm) is very different from the RI-PBE result of ref (520 nm). This difference can be attributed to the C 2 v constraint of the geometry optimization, but more plausibly to the RI-PBE approximation of ref .…”
Section: Absorption Spectra Of the Chini Clusterscontrasting
confidence: 90%
“…This fact must be attributed to the DFT issue. Nevertheless, a Hartree−Fock and B3LYP investigation of the structures coupled with new experiments has been published, as well as, recently, a RI-PBE (RI: resolution of the identity) investigation of the excited states of the clusters with n = 3−5, but with discussion of the colors of the clusters only, not of the actual spectra . In Table we give the main geometrical parameters of the Chini cluster [Pt 3 (CO) 6 ] 2 2− , obtained with the three functionals PBE, B3LYP, and MPW1K.…”
Section: Carbonylated Platinum: the Dft Issuementioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that solvoluminescence involves energy storage that is facilitated by charge-carrier mobility along the gold chains . Despite significant interest in this system, only limited theoretical studies have been reported to date. , …”
mentioning
confidence: 99%
“…[75] Mendizabal and coworkers studied the noncovalent interaction between several d 10 -d 10 macrocycles and arene fragments, denoting the nature of their formation. [56,[76][77][78][79][80][81][82] 2.4 | d 10 -d 10…”
Section: Host-guest Interactionmentioning
confidence: 99%